2022
DOI: 10.3390/jcm11226629
|View full text |Cite
|
Sign up to set email alerts
|

Buccolingual Inclination of Second Molars in Untreated Adolescents and Adults with Near Normal Occlusion: A CBCT Study

Abstract: The mandibular second molars are lingually positioned relative to the alveolar ridge and have a limited amount of lingual alveolar bony support. As the maxillary second molars are articulated with the mandibular second molars, maintaining the normal buccolingual inclination of both maxillary and mandibular second molars would potentially help to not only optimize the masticatory function, but also avoid dehiscence and fenestration. The current study evaluated the buccolingual inclination of second molars in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
0
0
Order By: Relevance
“…More recently, in a CBCT study including adolescent and adult patients, it was found in all patients that the maxillary second molar showed buccal inclination, and the mandibular second molar showed lingual inclination [25]. These findings provide a rationale for the occurrence of lingual fenestrations in the lower teeth as identified in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…More recently, in a CBCT study including adolescent and adult patients, it was found in all patients that the maxillary second molar showed buccal inclination, and the mandibular second molar showed lingual inclination [25]. These findings provide a rationale for the occurrence of lingual fenestrations in the lower teeth as identified in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…Wilson's curve is the name given to this occlusal curve in the coronal plane [ 6 ]. The natural curvature of the teeth is thought to allow the posterior teeth inclination to line up with the orientation and inward pull of the medial pterygoid muscle during contraction [ 7 ]. This provides optimal resistance to masticatory forces, facilitates access to food for efficient chewing, and ensures effective cuspal contact engagement [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research investigations addressing the inclinations of the posterior teeth have frequently divided their participants into groups based on sagittal [ 1 , 10 - 12 ] or vertical [ 2 , 13 - 17 ] skeletal features. Conversely, certain studies have examined inclinations without explicitly determining sagittal or vertical classification [ 5 - 7 , 18 , 19 ]. The majority of earlier studies have only used model casts to evaluate buccolingual inclination based on tooth crowns [ 1 , 10 - 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation